Electricity storage device and method for manufacturing electricity storage device

By adjusting the linear expansion coefficient and bending modulus of the resin material, the cracking problem during insert molding is solved, the sealing of the battery is ensured, and the stable molding of the first resin member and the second resin member is achieved.

CN119518239APending Publication Date: 2025-02-25PRIME PLANET ENERGY & SOLUTIONS INC +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410526899.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-09
Filing Date
2024-04-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When the insert is formed, the first resin member and the second resin member are prone to cracking, resulting in damage to the sealing properties of the battery.

Method used

Different resin materials are used to mold the first resin member and the second resin member, and the linear expansion coefficient and bending modulus of the resin material are adjusted respectively to ensure that no crack occurs during the insert molding. Specifically, the linear expansion coefficient of the first resin material is within the range of 1.6×10-5 to 2.7×10-5 (1/K), and the bending modulus of the second resin material is 17 GPa or less.

Benefits of technology

Cracking of the first resin member and the second resin member during insert molding is effectively avoided, and good sealing between the positive electrode terminal member and the first resin member and the negative electrode terminal member and the second resin member is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518239A_ABST
    Figure CN119518239A_ABST
Patent Text Reader

Abstract

The invention relates to an electricity storage device and a method for manufacturing the electricity storage device. The electricity storage device includes a housing member, a first terminal member, a second terminal member, a first resin member hermetically joined to the housing member and the first terminal member, and a second resin member hermetically joined to the housing member and the second terminal member. The first resin member is composed of a first resin material having a resin material linear expansion coefficient alpha in the range of 1.6 * 10-5 to 2.7 * 10-5 (1 / K), and the second resin member is composed of a second resin material different from the first resin material and having a resin material flexural modulus E of 17 GPa or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electric storage device in which a first terminal member is fixed to a case member constituting a case via a first resin member and a second terminal member is fixed via a second resin member, and a method for manufacturing the electric storage device. Background Art

[0002] As a power storage device, a battery is known in which a positive terminal member is fixed to a shell member (specifically, a rectangular plate-shaped shell cover member) constituting a rectangular box-shaped shell via a first resin member, and a negative terminal member is fixed to the above-mentioned shell member via a second resin member. Specifically, the positive terminal member is inserted into a first insertion hole provided in the shell cover member, extending from the inside of the shell to the outside, and the first resin member insulates the shell cover member and the positive terminal member, and at the same time, is airtightly joined to them, and the positive terminal member is fixed to the shell cover member. In addition, the negative terminal member is inserted into a second insertion hole provided in the shell cover member, extending from the inside of the shell to the outside, and the second resin member insulates the shell cover member and the negative terminal member, and at the same time, is airtightly joined to them, and the negative terminal member is fixed to the shell cover member.

[0003] When manufacturing such a battery, the first resin member and the second resin member are sometimes insert-molded. That is, in a state where the positive terminal member is inserted into the first insertion hole of the case cover member and the negative terminal member is inserted into the second insertion hole of the case cover member, the first resin member and the second resin member are simultaneously insert-molded using a single resin material. In addition, as a conventional technology for simultaneously insert-molding the first resin member and the second resin member using a single resin material, for example, Patent Document 1 can be cited.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2022-079172 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, during the insert molding, it is known that cracks (crazing) may occur along the boundary of the first resin member and the positive terminal member due to cohesion failure, or cracks (crazing) may occur along the boundary of the second resin member and the negative terminal member due to cohesion failure. If such cracks occur during insert molding, the cracks may further extend during actual use of the battery, and there is a possibility that the seal between the positive terminal member and the first resin member, and the seal between the negative terminal member and the second resin member may be damaged.

[0009] Furthermore, the linear expansion coefficients and the like are different between the positive terminal member made of aluminum and the negative terminal member made of copper. Therefore, it can also be seen that when a single resin material is used to mold the first resin member and the second resin member, if the resin material used for insert molding is adjusted so that the first resin member on the positive electrode side does not generate the above-mentioned cracks, the above-mentioned cracks are likely to occur in the second resin member on the negative electrode side. On the contrary, if the above-mentioned resin material is adjusted so that the above-mentioned cracks are not generated in the second resin member on the negative electrode side, the above-mentioned cracks are likely to occur in the first resin member on the positive electrode side.

[0010] The present invention has been completed in view of the current situation, and provides a storage device and a method for manufacturing the storage device, in which cracks are unlikely to occur in the first resin member and the second resin member during insert molding, and the sealing properties between the first terminal member composed of aluminum and the first resin member and the sealing properties between the second terminal member composed of copper and the second resin member can be well maintained.

[0011] Means for solving problems

[0012] (1) One solution of the present invention for solving the above-mentioned problems is a power storage device, comprising: a shell member having a first insertion hole and a second insertion hole; a first terminal member made of aluminum and inserted into the first insertion hole of the shell member; a second terminal member made of copper and inserted into the second insertion hole of the shell member; a first resin member which is insert-molded to insulate the shell member from the first terminal member and to bond them airtightly to fix the first terminal member to the shell member; and a second resin member which is insert-molded to insulate the shell member from the second terminal member and to bond them airtightly to fix the second terminal member to the shell member, wherein the first resin member is made of a resin material having a linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 (1 / K) range (1.6×10 -5 ≤α≤2.7×10 -5 ), and the second resin member is composed of a second resin material different from the first resin material and having a resin material flexural modulus E of 17 GPa or less (E≤17).

[0013] As described above, conventionally, a single resin material is used to mold the first resin member and the second resin member, so that the sealing performance between the first terminal member and the first resin member and the sealing performance between the second terminal member and the second resin member cannot be taken into consideration. In the above-mentioned power storage device, different resin materials are used to mold the first resin member and the second resin member. Furthermore, the linear expansion coefficient α of the first resin material forming the first resin member is set to 1.6×10-5 ~2.7×10 -5 (1 / K), the bending modulus E of the resin material of the second resin material forming the second resin member is made less than 17 GPa. As a result, cracks are less likely to occur in the first resin member and the second resin member during insert molding, and the sealing performance between the first terminal member and the first resin member and the sealing performance between the second terminal member and the second resin member can be well maintained.

[0014] The reason for this is not necessarily clear at present. The present inventors have studied the linear expansion coefficient α of the resin material used for insert molding, the bending modulus E of the resin material, and the sealing performance between the terminal member and the resin member (refer to Figure 11 to Figure 14 ). This will be described in detail later.

[0015] As a result, in relation to the first terminal member made of aluminum, the magnitude of the flexural modulus E of the first resin material does not greatly affect the sealing performance between the first terminal member and the first resin member (see Fig.12 On the other hand, the linear expansion coefficient α of the first resin material has a great influence on the sealing performance between the first terminal member and the first resin member (see Fig.11 ), it can be seen that by setting the value of the linear expansion coefficient α of the resin material within the above range, the sealing performance can be well maintained.

[0016] In addition, in relation to the second terminal member made of copper, the linear expansion coefficient α of the second resin material does not greatly affect the sealing performance between the second terminal member and the second resin member (see Fig.14 On the other hand, the bending modulus E of the second resin material has a great influence on the sealing performance between the second terminal member and the second resin member (refer to Fig.13 ), it can be seen that by making the value of the flexural modulus E of the resin material within the above range, the sealing performance can be well maintained.

[0017] The temperature range of the "resin material linear expansion coefficient α" of the first resin material is -40 to 65° C. A specific method for measuring the resin material linear expansion coefficient α will be described later.

[0018] The “resin material flexural modulus E” of the second resin material is obtained by performing a three-point bending test using a test piece (length 10 mm×width 1.5 mm×thickness 1.5 mm) of the second resin material. A specific method for measuring the resin material flexural modulus E will be described later.

[0019] The flexural modulus E of the second resin material is preferably greater than 10 GPa (10 ≤ E ≤ 17). This is because if the flexural modulus E of the resin material is too small, the strength of the second resin component is likely to be greatly reduced, and the stress generated in the second resin component during insert molding may exceed the strength of the second resin component, causing cracks in the second resin component.

[0020] Examples of the “electricity storage device” include secondary batteries such as lithium ion secondary batteries, sodium ion secondary batteries, and calcium ion secondary batteries, and capacitors such as lithium ion capacitors.

[0021] (2) The power storage device according to (1), wherein the first resin material includes a first thermoplastic main resin, a first thermoplastic elastomer, and a first filler, and the second resin material includes a second thermoplastic main resin, a second thermoplastic elastomer, and a second filler.

[0022] As described above, by making the first resin material a resin material having a thermoplastic first elastomer and a first filler in addition to a thermoplastic first main resin, the size of the resin material linear expansion coefficient α of the first resin material can be easily adjusted. In addition, by making the second resin material a resin material having a thermoplastic second elastomer and a second filler in addition to a thermoplastic second main resin, the size of the resin material bending modulus E of the second resin material can be easily adjusted.

[0023] It should be noted that the "main resin" refers to the material that has the largest weight ratio among the materials constituting the resin material, excluding the filler. Examples of the "thermoplastic main resin" include thermoplastic resins such as polyethylene (PE), polypropylene (PP), polybutylene (PB), polyphenylene sulfide (PPS), polytetrafluoroethylene (PTFE), and perfluoroalkoxyalkane (PFA).

[0024] Examples of "thermoplastic elastomers" include thermoplastic polyurethane elastomers (TPU) obtained from diisocyanates such as 4,4'-diphenylmethane diisocyanate (MDI) and high molecular weight diols. Examples of high molecular weight diols include polyester diol (PES), polyether diol (PET), polycaprolactone diol (PCL), and polycarbonate diol (PCD).

[0025] Examples of the “filler” include glass fillers made of alkali glass or E glass, alumina fillers made of alumina, potassium titanate fillers made of potassium titanate, etc. Examples of the shape of the “filler” include spherical, plate-like, fibrous, and needle-like shapes.

[0026] The first resin material may include materials other than the first main resin, the first elastomer, and the first filler described above. In addition, the second resin material may include materials other than the second main resin, the second elastomer, and the second filler described above.

[0027] (3) An electric storage device according to (1) or (2), wherein the first terminal member has a first terminal sealing portion, the first resin member is airtightly bonded to the first terminal sealing portion, and on the surface of the first terminal sealing portion, particles containing aluminum having a diameter of less than 100 nm are connected in a rosary-like manner to form a columnar forest of first nanocolumns with a height of more than 50 nm, the first resin material is filled between the first nanocolumns in the forest, and the first resin member is airtightly bonded to the first terminal sealing portion, and the second terminal member has a second terminal sealing portion, the second resin member is airtightly bonded to the second terminal sealing portion, and on the surface of the second terminal sealing portion, particles containing copper having a diameter of less than 100 nm are connected in a rosary-like manner to form a columnar forest of second nanocolumns with a height of more than 50 nm, the second resin material is filled between the second nanocolumns in the forest, and the second resin member is airtightly bonded to the second terminal sealing portion.

[0028] In the above-mentioned power storage device, the above-mentioned first nanocolumns are arranged on the surface of the first terminal sealing portion of the first terminal member, the first resin material is filled between these first nanocolumns, and the first resin member is airtightly bonded to the first terminal sealing portion. Thus, the bonding strength between the first terminal sealing portion of the first terminal member and the first resin member can be improved, and the sealing performance between the first terminal member and the first resin member can be particularly well maintained.

[0029] In addition, the second nanocolumns are arranged on the surface of the second terminal sealing portion of the second terminal member, the second resin material is filled between the second nanocolumns, and the second resin member is airtightly bonded to the second terminal sealing portion. Thus, the bonding strength between the second terminal sealing portion of the second terminal member and the second resin member can be improved, and the sealing performance between the second terminal member and the second resin member can be particularly well maintained.

[0030] Furthermore, examples of “aluminum-containing particles” constituting the first nanocolumn include particles consisting of aluminum, particles consisting of aluminum oxide, particles consisting of aluminum and aluminum oxide, etc. In addition, examples of “copper-containing particles” constituting the second nanocolumn include particles consisting of copper, particles consisting of copper oxide, particles consisting of copper and copper oxide, etc.

[0031] (4) In addition, another embodiment of the present invention is a method for manufacturing an electric storage device, the electric storage device comprising: a shell member having a first insertion hole and a second insertion hole; a first terminal member made of aluminum and inserted into the first insertion hole of the shell member; a second terminal member made of copper and inserted into the second insertion hole of the shell member; a first resin member insert-molded to insulate the shell member from the first terminal member and to bond them airtightly to fix the first terminal member to the shell member; and a second resin member insert-molded to insulate the shell member from the second terminal member and to bond them airtightly to fix the second terminal member to the shell member, wherein the first resin member is made of a resin material having a linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 (1 / K) range (1.6×10 -5 ≤α≤2.7×10 -5 ), the second resin member is composed of a second resin material different from the first resin material and having a resin material bending modulus E of 17 GPa or less (E≤17), the manufacturing method of the power storage device comprising: a first insert molding process, wherein, with the first terminal member inserted into the first insertion hole of the shell member, the first resin member is insert-molded using the first resin material having a linear expansion coefficient α of the resin material; and a second insert molding process, wherein, with the second terminal member inserted into the second insertion hole of the shell member, the second resin member is insert-molded using the second resin material having a resin material bending modulus E.

[0032] In the manufacturing method of the above-mentioned power storage device, in the first insert molding process, the first resin member is insert-molded using the first resin material having the linear expansion coefficient α of the above-mentioned resin material, so that it is difficult to generate cracks in the first resin member during molding, and the sealing performance between the first terminal member and the first resin member can be well maintained. In addition, in the second insert molding process, the second resin member is insert-molded using the second resin material having the bending modulus E of the above-mentioned resin material, so that it is difficult to generate cracks in the second resin member during molding, and the sealing performance between the second terminal member and the second resin member can be well maintained. In addition, the first insert molding process and the second insert molding process can be performed separately or simultaneously.

[0033] (5) The method for manufacturing an electric storage device according to (4), wherein the second insert molding step is performed first, and then the first insert molding step is performed.

[0034] The first terminal member made of aluminum has a larger linear expansion coefficient than the second terminal member made of copper. Therefore, if the first insert molding process is performed first, cracks are likely to occur in the first resin member due to temperature changes in the subsequent second insert molding process. In the above-mentioned method for manufacturing the power storage device, since the second insert molding process is performed first, the first resin member does not exist in the second insert molding process, and cracks will not occur in the first resin member.

[0035] (6) A method for manufacturing an electrical storage device according to (4) or (5), wherein the first terminal member has a first terminal sealing portion, the first resin member is airtightly bonded to the first terminal sealing portion, on the surface of the first terminal sealing portion, particles containing aluminum having a diameter of less than 100 nm are connected in a rosary-like manner to form a columnar forest of first nanocolumns with a height of more than 50 nm, the first resin material is filled between the first nanocolumns in the forest, the first resin member is airtightly bonded to the first terminal sealing portion, the second terminal member has a second terminal sealing portion, the second resin member is airtightly bonded to the second terminal sealing portion, on the surface of the second terminal sealing portion, particles containing copper having a diameter of less than 100 nm are connected in a rosary-like manner to form a columnar forest of second nanocolumns with a height of more than 50 nm, the second resin material is filled between the second nanocolumns in the forest, and the second resin member is airtightly bonded to the second terminal sealing portion. The manufacturing method of the energy storage device further includes: a first nanocolumn forming process, wherein, before the first insert molding process, the first terminal sealing portion of the first terminal member is irradiated with a pulsed oscillating laser while shifting the irradiation position, so as to form a forest of the first nanocolumns in the first terminal sealing portion; and a second nanocolumn forming process, wherein, before the second insert molding process, the second terminal sealing portion of the second terminal member is irradiated with a pulsed oscillating laser while shifting the irradiation position, so as to form a forest of the second nanocolumns in the second terminal sealing portion, the first insert molding process fills the first resin material between the first nanocolumns in the first terminal sealing portion and molds the first resin member at the same time, and the second insert molding process fills the second resin material between the second nanocolumns in the second terminal sealing portion and molds the second resin member at the same time.

[0036] In the manufacturing method of the above-mentioned power storage device, the laser is irradiated as described above in the first nanocolumn forming step to form the above-mentioned first nanocolumn on the surface of the first terminal sealing portion, so that the first nanocolumn can be easily formed on the first terminal sealing portion. In addition, in the first insert molding step, the first resin material is filled between the first nanocolumns and the first resin member is molded at the same time, so that the bonding strength between the first terminal sealing portion of the first terminal member and the first resin member can be improved, and the sealing performance between the first terminal member and the first resin member can be particularly well maintained.

[0037] In addition, in the second nanocolumn forming step, the laser is irradiated as described above to form the second nanocolumn on the surface of the second terminal sealing portion, so that the second nanocolumn can be easily formed on the second terminal sealing portion. In addition, in the second insert molding step, the second resin material is filled between the second nanocolumns and the second resin member is molded at the same time, so that the bonding strength between the second terminal sealing portion of the second terminal member and the second resin member can be improved, and the sealing performance between the second terminal member and the second resin member can be particularly well maintained. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a perspective view of a battery according to an embodiment.

[0039] Figure 2 It is a partial cross-sectional view of the battery according to the embodiment along the battery height direction and the battery width direction.

[0040] Figure 3A It is a partial enlarged cross-sectional view of the vicinity of the positive electrode terminal member (negative electrode terminal member) and the first resin member (second resin member) in the battery according to the embodiment, and is a partial enlarged cross-sectional view along the battery height direction and the battery width direction.

[0041] Figure 3B It is a partial enlarged cross-sectional view of the vicinity of the positive electrode terminal member (negative electrode terminal member) and the first resin member (second resin member) in the battery according to the embodiment, and is a partial enlarged cross-sectional view along the battery height direction and the battery thickness direction.

[0042] Figure 4 This is an enlarged cross-sectional view of a portion near the surface of a positive electrode terminal sealing portion (negative electrode terminal sealing portion, first cover sealing portion, second cover sealing portion) in the battery according to the embodiment.

[0043] Figure 5 This is an explanatory diagram of a cross section of a first resin material (second resin material) showing a method for measuring a linear expansion coefficient α and a flexural modulus E of a resin material.

[0044] Figure 6 It is an explanatory diagram showing a method for measuring the flexural modulus E of a resin material.

[0045] Figure 7 This is a flow chart of a method for manufacturing a battery according to an embodiment.

[0046] Figure 8 It is an explanatory diagram showing a positive electrode nanocolumn forming step (a negative electrode nanocolumn forming step, a cap nanocolumn forming step) of a method for manufacturing a battery according to an embodiment.

[0047] Fig.9A This is an explanatory diagram of the second insert molding step of the battery manufacturing method according to the embodiment, and shows a state in which a negative electrode terminal member is inserted into a second insertion hole of a case cover member.

[0048] Fig. 9B This is an explanatory diagram of the second insert molding step of the battery manufacturing method according to the embodiment, and shows how the second resin member is molded.

[0049] Fig. 10A This is an explanatory diagram of a first insert molding step of the battery manufacturing method according to the embodiment, and shows a state in which a positive electrode terminal member is inserted into a first insertion hole of a case cover member.

[0050] Fig. 10B This is an explanatory diagram of a first insert molding step of the battery manufacturing method according to the embodiment, and shows how a first resin member is molded.

[0051] Fig.11 Graph showing the relationship between the linear expansion coefficient α of the first resin material of the positive electrode and the length of cracks generated in the first resin member after the thermal cycle test.

[0052] Fig.12 Graph showing the relationship between the resin material flexural modulus E of the first resin material of the positive electrode and the length of cracks generated in the first resin member after the thermal cycle test.

[0053] Fig.13 Graph showing the relationship between the resin material flexural modulus E of the second resin material of the negative electrode and the length of cracks generated in the second resin member after the thermal cycle test.

[0054] Fig.14 Graph showing the relationship between the resin material linear expansion coefficient α of the second resin material of the negative electrode and the length of cracks generated in the second resin member after the thermal cycle test.

[0055] Description of Reference Numerals

[0056] 1 Battery (power storage device)

[0057] 10 Housing

[0058] 30 Shell cover member (shell member)

[0059] 30h1 First insertion hole

[0060] 30h2 Second insertion hole

[0061] 40 Electrode body

[0062] 50 positive terminal member (first terminal member)

[0063] 52 positive terminal sealing portion (first terminal sealing portion)

[0064] 52m (Surface of positive terminal seal) 55 Positive electrode nanorod (first nanorod)

[0065] 55p Particles

[0066] 60 Negative terminal member (second terminal member)

[0067] 62 Negative terminal sealing portion (second terminal sealing portion)

[0068] 62m Surface (of the negative terminal seal) 65 Negative electrode nanocolumn (second nanocolumn)

[0069] 65p Particles

[0070] 70 first resin member

[0071] 75 First resin material

[0072] 76 First Main Resin

[0073] 77 First Elastic Body

[0074] 78 First Filler

[0075] 80 Second resin member

[0076] 85 Second resin material

[0077] 86 Second main resin

[0078] 87 Second elastic body

[0079] 88 Second filler

[0080] α Linear expansion coefficient of resin material

[0081] E Resin material flexural modulus

[0082] LC Laser

[0083] S1: Positive electrode nanocolumn forming step (first nanocolumn forming step) S2 Negative electrode nanocolumn forming step (second nanocolumn forming step) S4 Second Insert Molding Process

[0084] S5 First insert molding process DETAILED DESCRIPTION

[0085] Hereinafter, embodiments of the present invention will be described with reference to the drawings. Figure 1 , which is a perspective view of a battery (electricity storage device) 1 according to this embodiment, Figure 2 A partial cross-sectional view of the battery 1 is shown in FIG. Figure 3A and Figure 3B FIG. 5 is an enlarged cross-sectional view of a portion of the positive electrode terminal member 50 (negative electrode terminal member 60) and the first resin member 70 (second resin member 80) and the vicinity thereof. Figure 4 FIG. 2 is an enlarged cross-sectional view of a portion near the surface 52m (surface 62m) of the positive terminal sealing portion 52 (negative terminal sealing portion 62). It should be noted that, hereinafter, the battery height direction AH, the battery width direction BH, and the battery thickness direction CH of the battery 1 are defined as Figure 1 and Figure 2 The battery 1 is a square (rectangular parallelepiped) sealed lithium ion secondary battery mounted on a vehicle such as a hybrid vehicle, a plug-in hybrid vehicle, or an electric vehicle.

[0086] The battery 1 is composed of a housing 10, an electrode body 40 housed in the housing 10, a positive terminal member (first terminal member) 50 fixed to the housing 10 via a first resin member 70, and a negative terminal member (second terminal member) 60 fixed to the housing 10 via a second resin member 80. The electrode body 40 is covered by a bag-shaped insulating holder 7 composed of an insulating film in the housing 10. In addition, an electrolyte 5 is housed in the housing 10, a part of the electrolyte 5 is impregnated (immersed) in the electrode body 40, and the remaining electrolyte 5 is accumulated on the bottom wall of the housing 10.

[0087] The case 10 is a rectangular box made of metal (aluminum in this embodiment), and is a bottomed square tube with a rectangular opening 20c. It is composed of a case body member 20 that accommodates the electrode body 40 inside, and a rectangular plate-shaped case cover member 30 that plugs the opening 20c of the case body member 20. In this embodiment, the case cover member 30 is equivalent to the above-mentioned "case member". The opening 20c of the case body member 20 and the peripheral edge 30f of the case cover member 30 are welded airtightly throughout the entire circumference.

[0088] The housing cover member 30 of the housing 10 is provided with a safety valve 11 that breaks and opens when the internal pressure of the housing 10 exceeds the valve opening pressure. In addition, the housing cover member 30 is provided with a liquid injection hole 30k that penetrates the housing cover member 30, and the liquid injection hole 30k is hermetically sealed with a disc-shaped sealing member 12 made of aluminum.

[0089] The electrode body 40 accommodated in the housing 10 is a rectangular parallelepiped, laminated type, and is formed by alternately laminating a plurality of positive electrode plates 41 and a plurality of negative electrode plates 42 in the battery thickness direction CH via a separator (partition plate) 43 composed of a porous film made of resin. The positive electrode plate 41, the negative electrode plate 42, and the separator 43 are each rectangular extending in the battery height direction AH and the battery width direction BH.

[0090] The positive electrode plate 41 is composed of a positive electrode collector foil made of aluminum foil and a positive electrode active material layer containing positive electrode active material particles formed on both main surfaces of the positive electrode collector foil. A portion of the positive electrode collector foil extends out on one side BH1 in the battery width direction BH, forming a positive electrode foil exposed portion exposed on both main surfaces without the positive electrode active material layer. Moreover, the positive electrode foil exposed portions of each positive electrode plate 41 overlap in the foil thickness direction, forming a positive electrode collector portion 40c. The positive electrode collector portion 40c is electrically connected to the positive terminal member 50 described later.

[0091] In addition, the negative electrode plate 42 is composed of a negative electrode collector foil composed of copper foil and a negative electrode active material layer containing negative electrode active material particles formed on both main surfaces of the negative electrode collector foil. A portion of the negative electrode collector foil extends out on the other side BH2 in the battery width direction BH, forming a negative electrode foil exposed portion exposed without the negative electrode active material layer on both main surfaces. Moreover, the negative electrode foil exposed portions of each negative electrode plate 42 overlap in the foil thickness direction, forming a negative electrode collector portion 40d. The negative electrode collector portion 40d is conductively connected to the negative terminal member 60 described later.

[0092] In the case cover member 30, a rectangular first insertion hole 30h1 penetrating the case cover member 30 is provided near the end of one side BH1 in the battery width direction BH, and a rectangular second insertion hole 30h2 penetrating the case cover member 30 is provided near the end of the other side BH2 in the battery width direction BH. Among them, the positive terminal member 50 made of aluminum is inserted into the first insertion hole 30h1, and the positive terminal member 50 is fixed to the case cover member 30 in a state of being insulated from the case cover member 30 via the first resin member 70. In addition, the negative terminal member 60 made of copper is inserted into the second insertion hole 30h2, and the negative terminal member 60 is fixed to the case cover member 30 in a state of being insulated from the case cover member 30 via the second resin member 80.

[0093] First, the positive electrode will be described. The positive electrode terminal member 50 (excluding Figure 1 and Figure 2 In addition, also refer to Figure 3A and Figure 3B ) is a member formed by pressing an aluminum plate, and is composed of a positive terminal outer portion 51, a positive terminal inner portion 53, and a positive terminal sealing portion (first terminal sealing portion) 52. The rectangular plate-shaped positive terminal outer portion 51 is located on the outer side of the case cover member 30 (the upper side AH1 in the battery height direction AH) and extends in the battery width direction BH and the battery thickness direction CH. The positive terminal inner portion 53 is located on the inner side of the case cover member 30 (the lower side AH2 in the battery height direction AH) and extends in the battery height direction AH. The positive terminal sealing portion (first terminal sealing portion) 52 is connected to the positive terminal outer portion 51 and the positive terminal inner portion 53 via the first insertion hole 30h1. The positive terminal sealing portion 52 is bent at the end of the positive terminal outer portion 51 on one side CH1 in the battery thickness direction CH, and extends to the lower side AH2, so that the first resin member 70 described later passes through the battery height direction AH. Furthermore, the positive electrode terminal inner portion 53 is welded to the positive electrode current collecting portion 40 c of the electrode body 40 at the tip end portion of the lower side AH2 and is conductively connected to the positive electrode current collecting portion 40 c.

[0094] The surface 51m of the positive terminal outer portion 51 has a rectangular top surface 51ma facing the upper side AH1, a rectangular inner side surface 51mb facing the lower side AH2, and an end surface 51mc connecting them, wherein the positive terminal outer portion 51 is bonded to the first resin member 70 at the inner side surface 51mb and the end surface 51mc. However, in the present embodiment, the positive electrode nanocolumns described later are not formed on these inner side surfaces 51mb and the end surface 51mc.

[0095] On the other hand, the first resin member 70 is airtightly bonded to the positive terminal sealing portion 52. Specifically, the surface 52m of the positive terminal sealing portion 52 has: a first main surface 52ma facing one side CH1 in the battery thickness direction CH, a second main surface 52mb facing the other side CH2 in the battery thickness direction CH, and a pair of end surfaces 52mc connecting them. Figure 4 As shown, particles 55p formed of aluminum and aluminum oxide are connected in a rosary-like manner to form a columnar positive electrode nanocolumn (first nanocolumn) 55. The diameter Da of the particle 55p is less than 100nm (in this embodiment, approximately Da=30nm), and the height ha of the positive electrode nanocolumn 55 is greater than 50nm (in this embodiment, approximately ha=200nm). As for the first resin member 70 described later, the first resin material 75 is filled between these forested positive electrode nanocolumns 55 and is airtightly bonded to the positive terminal sealing portion 52.

[0096] In addition, in the case cover member 30, the first resin member 70 and the first cover seal portion 31 (see Figure 3A and Figure 3B ) are joined airtightly. Specifically, the first cover sealing portion 31 has: a rectangular annular outer side surface 31m facing outward (upper side AH1), and a rectangular annular inner side surface 31n facing inward (lower side AH2). On these surfaces 31m, 31n, similarly to the surface 52m of the positive terminal sealing portion 52 (see Figure 4 ), the particles 35p formed of aluminum and aluminum oxide are connected in a rosary-like manner to form a columnar first cover nano-pillar 35. The diameter Da of the particle 35p is less than 100nm (in this embodiment, approximately Da=30nm), and the height ha of the first cover nano-pillar 35 is greater than 50nm (in this embodiment, approximately ha=200nm). As for the first resin member 70 described later, the first resin material 75 is filled between these first cover nano-pillars 35 standing in a forest, and is airtightly bonded to the first cover sealing portion 31.

[0097] Next, the negative electrode will be described. The negative electrode terminal member 60 has the same shape as the positive electrode terminal member 50 (see Figure 1 to Figure 3B ). The negative terminal member 60 is a member formed by pressing a copper plate, and is composed of a negative terminal outer portion 61, a negative terminal inner portion 63, and a negative terminal sealing portion (second terminal sealing portion) 62. The rectangular plate-shaped negative terminal outer portion 61 is located on the outer side (upper side AH1) of the shell cover member 30 and extends in the battery width direction BH and the battery thickness direction CH. The negative terminal inner portion 63 is located on the inner side (lower side AH2) of the shell cover member 30 and extends in the battery height direction AH. The negative terminal sealing portion (second terminal sealing portion) 62 is connected to the negative terminal outer portion 61 and the negative terminal inner portion 63 via the second insertion hole 30h2. The negative terminal sealing portion 62 is bent at the end of one side CH1 of the negative terminal outer portion 61 in the battery thickness direction CH, extends to the lower side AH2, and penetrates the second resin member 80 described later in the battery height direction AH. Furthermore, the negative electrode terminal inner portion 63 is welded to the negative electrode current collecting portion 40 d of the electrode body 40 at the tip portion of the lower side AH2 and is conductively connected to the negative electrode current collecting portion 40 d.

[0098] The surface 61m of the negative terminal outer portion 61 has a rectangular top surface 61ma facing the upper side AH1, a rectangular inner side surface 61mb facing the lower side AH2, and an end surface 61mc connecting them, wherein the negative terminal outer portion 61 is bonded to the second resin member 80 at the inner side surface 61mb and the end surface 61mc. However, in the present embodiment, the negative electrode nanocolumns described later are not formed on these inner side surfaces 61mb and the end surface 61mc.

[0099] On the other hand, the second resin member 80 is airtightly bonded to the negative terminal sealing portion 62. Specifically, the surface 62m of the negative terminal sealing portion 62 has a first main surface 62ma facing one side CH1 in the battery thickness direction CH, a second main surface 62mb facing the other side CH2 in the battery thickness direction CH, and a pair of end surfaces 62mc connecting them. Figure 4 ), particles 65p formed of copper and copper oxide are connected in a rosary-like manner to form a columnar negative electrode nanocolumn (second nanocolumn) 65. The diameter Da of the particle 65p is less than 100nm (in this embodiment, approximately Da=30nm), and the height ha of the negative electrode nanocolumn 65 is greater than 50nm (in this embodiment, approximately ha=200nm). As for the second resin member 80 described later, the second resin material 85 is filled between these forested negative electrode nanocolumns 65 and is airtightly bonded to the negative terminal sealing portion 62.

[0100] In addition, in the case cover member 30, the second resin member 80 and the second cover seal portion 32 (see Figure 3A and Figure 3B ) are joined airtightly. Specifically, the second cover seal portion 32 has: a rectangular annular outer side surface 32m facing outward (upper side AH1), and a rectangular annular inner side surface 32n facing inward (lower side AH2). On these surfaces 32m, 32n, similarly to the outer side surface 31m and the inner side surface 31n of the first cover seal portion 31 (see Figure 4 ), the particles 36p formed of aluminum and aluminum oxide are connected in a rosary-like manner to form a columnar second cover nano-pillar 36. The diameter Da of the particle 36p is less than 100nm (in this embodiment, approximately Da=30nm), and the height ha of the second cover nano-pillar 36 is greater than 50nm (in this embodiment, approximately ha=200nm). As for the second resin member 80 described later, the second resin material 85 is filled between these second cover nano-pillars 36 that are lined up, and is airtightly bonded to the second cover sealing portion 32.

[0101] Next, the first resin member 70 of the positive electrode will be described (see Figure 1 to Figure 4). The first resin member 70 insulates the case cover member 30 and the positive terminal member 50, and is bonded to the case cover member 30 and the positive terminal member 50, thereby fixing the positive terminal member 50 to the case cover member 30. In detail, the first resin material 75 described later is filled between the positive electrode nano-pillars 55 standing in a forest of the positive terminal sealing portion 52 of the positive terminal member 50, and the first resin member 70 is airtightly bonded to the positive terminal sealing portion 52. In addition, the first resin material 75 is filled between the first cover nano-pillars 35 standing in a forest of the first cover sealing portion 31 of the case cover member 30, and the first resin member 70 is airtightly bonded to the first cover sealing portion 31.

[0102] The first resin member 70 is composed of a first resin outer portion 71 located on the outer side (upper side AH1) of the housing cover member 30, and a first resin inner portion 72 located on the inner side (lower side AH2) of the housing cover member 30 and in the first insertion hole 30h1 and connected to the first resin outer portion 71. The first resin member 70 is made of a resin material having a linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 In this embodiment, α=2.3×10 -5 (1 / K).

[0103] The first resin material 75 is composed of a thermoplastic first main resin 76, a thermoplastic first elastomer 77, and a first filler 78. Specifically, in the present embodiment, the first main resin 76 is polyphenylene sulfide (PPS). In addition, the first elastomer 77 is a thermoplastic polyurethane elastomer (TPU) obtained from 4,4'-diphenylmethane diisocyanate (MDI) and polyester diol (PES). In addition, the first filler 78 is a fibrous (approximately 10 μm in diameter × 300 μm in length) glass filler composed of alkali glass. In addition, the weight ratio of the first main resin 76, the first elastomer 77, and the first filler 78 is first main resin: first elastomer: first filler = 40:10:50.

[0104] Here, a method for measuring the linear expansion coefficient α of the first resin material 75 will be described (see Figure 5 ). In the present embodiment, the first filler 78 contained in the first resin material 75 is fibrous, so if the first filler 78 dispersed in the first resin material 75 is oriented, the linear expansion coefficient α of the first resin material 75 will be directional. That is, if the first filler 78 is oriented in the direction of surface expansion, the first direction MD ( Figure 5 The first direction linear expansion coefficient αM (the direction extending in the left-right direction and the direction perpendicular to the paper surface) and the second direction TD (the direction extending in the left-right direction and the direction perpendicular to the paper surface) perpendicular to the first direction MD Figure 5 Therefore, the first direction linear expansion coefficient αM and the second direction linear expansion coefficient αT are respectively obtained, and the average value is calculated and set as the resin material linear expansion coefficient α (α = (αM + αT) / 2).

[0105] Specifically, the first direction linear expansion coefficient αM and the second direction linear expansion coefficient αT of the first resin material 75 are calculated using the digital image correlation method (DIC). First, a rectangular test piece of the first resin material 75 in which the first filler 78 is oriented in the direction of surface expansion is prepared. The cross section along the first direction MD and the second direction TD can be seen (refer to Figure 5 ) is placed on a sample cooling and heating stage (e.g., 10083L, a large sample cooling and heating stage for microscope, manufactured by JAPAN HI-TECH Co., Ltd.). Then, an initial image of the cross section of the test piece at 25°C is obtained. The image is obtained using, for example, a digital microscope VHX-8000 manufactured by KEYANCE Co., Ltd.

[0106] Then, the test piece is cooled to -40°C and then heated to 65°C. Images of the cross section of the test piece are obtained at -40°C, 0°C, 25°C, 50°C, and 65°C. The obtained images are analyzed using a DIC system (e.g., DIC system ARAMIS manufactured by GOM), and an approximate straight line y=ax+b representing the relationship between temperature x and strain y is obtained for the first direction MD, and the slope a of the straight line is set as the first direction linear expansion coefficient αM for the first direction MD. In addition, an approximate straight line y=cx+d representing the relationship between temperature x and strain y is obtained for the second direction TD, and the slope c of the straight line is set as the second direction linear expansion coefficient αT for the second direction TD. Furthermore, the average value ((αM+αT) / 2) of these is calculated and set as the linear expansion coefficient α of the resin material.

[0107] Next, the second resin member 80 of the negative electrode will be described (see Figure 1 to Figure 4 ). The second resin member 80 insulates the case cover member 30 from the negative terminal member 60, and is bonded to the case cover member 30 and the negative terminal member 60 to fix the negative terminal member 60 to the case cover member 30. In detail, the second resin material 85 described later is filled between the forest of negative electrode nano-pillars 65 of the negative terminal sealing portion 62 of the negative terminal member 60, and the second resin member 80 is airtightly bonded to the negative terminal sealing portion 62. In addition, the second resin material 85 is filled between the forest of second cover nano-pillars 36 of the second cover sealing portion 32 of the case cover member 30, and the second resin member 80 is airtightly bonded to the second cover sealing portion 32.

[0108] The second resin member 80 has the same shape as the first resin member 70. The second resin member 80 is composed of a second resin outer portion 81 located on the outer side (upper side AH1) of the housing cover member 30, and a second resin inner portion 82 located on the inner side (lower side AH2) of the housing cover member 30 and in the second insertion hole 30h2 and connected to the second resin outer portion 81. The second resin member 80 is composed of a second resin material 85 different from the first resin material 75, whose resin material bending modulus E is 17 GPa or less. Furthermore, the resin material bending modulus E of the second resin material 85 is set to 10 GPa or more. Specifically, in the present embodiment, E=16 GPa.

[0109] The second resin material 85 is composed of a thermoplastic second main resin 86, a thermoplastic second elastomer 87, and a second filler 88. In the present embodiment, the second main resin 86, the second elastomer 87, and the second filler 88 are respectively the same as the first main resin 76, the first elastomer 77, and the first filler 78 of the first resin material 75. However, the mixing ratio of the second main resin 86, the second elastomer 87, and the second filler 88 in the second resin material 85 is different from the mixing ratio of the first main resin 76, the first elastomer 77, and the first filler 78 in the first resin material 75. Specifically, the weight ratio of the second main resin 86, the second elastomer 87, and the second filler 88 is second main resin: second elastomer: second filler = 40:15:45.

[0110] Here, a method for measuring the flexural modulus E of the second resin material 85 will be described (see Figure 6 In this embodiment, since the second filler 88 contained in the second resin material 85 is fibrous, if the second filler 88 dispersed in the second resin material 85 is oriented, the bending modulus E of the resin material of the second resin material 85 will have directionality. That is, if the second filler 88 is oriented in the direction of surface expansion (refer to Figure 5 ), the first direction bending modulus EM in the first direction MD along the longitudinal direction of the second filler 88 and the second direction bending modulus ET in the second direction TD orthogonal to the first direction MD become different in size. Therefore, the first direction bending modulus EM and the second direction bending modulus ET are respectively obtained, and the average value is calculated and set as the resin material bending modulus E (E = (EM + ET) / 2).

[0111] Specifically, the first direction bending modulus EM and the second direction bending modulus ET are obtained by performing a three-point bending test. First, two rectangular test pieces (length 10 mm×width 1.5 mm×thickness 1.5 mm) of the second resin material 85 in which the second filler 88 is oriented in the direction of surface expansion are prepared. In one test piece, the first direction MD and the length direction ( Figure 6 center left and right direction) and width direction ( Figure 6 The second direction TD is consistent with the thickness direction of the test piece ( Figure 6 In another test piece, the second direction TD is consistent with the length direction of the test piece, and the first direction MD is consistent with the width direction and thickness direction of the test piece.

[0112] Next, at an ambient temperature of 23°C, a test piece of the second resin material 85 was placed on a pair of support parts SA with a support distance L of 8 mm, and the center of the length direction of the test piece was pressed from top to bottom with a force F of 1 kN using a pressing part SB. In addition, the radius R1 of the top end of the support part SA and the radius R2 of the top end of the pressing part SB were both 1.5 mm. For each test piece, the first direction bending modulus EM and the second direction bending modulus ET were obtained, and their average value ((EM+ET) / 2) was calculated and used as the resin material bending modulus E.

[0113] In the battery 1 of this embodiment, as described above, the first resin member 70 and the second resin member 80 are molded with different resin materials. In addition, the linear expansion coefficient α of the first resin material 75 forming the first resin member 70 is set to 1.6×10 -5 ~2.7×10 -5 (1 / K), the resin material bending modulus E of the second resin material 85 forming the second resin member 80 is set to 17 GPa or less. Furthermore, the resin material bending modulus E of the second resin material 85 is set to 10 GPa or more. As described later, cracks are unlikely to occur in the first resin member 70 and the second resin member 80 during insert molding, and the sealing properties between the positive terminal member 50 and the first resin member 70, and the sealing properties between the negative terminal member 60 and the second resin member 80 can be well maintained.

[0114] Furthermore, in the present embodiment, since the first resin material 75 is a resin material including the first thermoplastic elastomer 77 and the first filler 78 in addition to the first thermoplastic main resin 76, the size of the resin material linear expansion coefficient α of the first resin material 75 can be easily adjusted. In addition, since the second resin material 85 is a resin material including the second thermoplastic elastomer 87 and the second filler 88 in addition to the second thermoplastic main resin 86, the size of the resin material bending modulus E of the second resin material 85 can be easily adjusted.

[0115] In addition, in the present embodiment, the above-mentioned positive electrode nano-pillars 55 are arranged on the surface 52m of the positive electrode terminal sealing portion 52 of the positive electrode terminal member 50, and the first resin material 75 is filled between these positive electrode nano-pillars 55, and the first resin member 70 is airtightly bonded to the positive electrode terminal sealing portion 52. Thus, the bonding strength between the positive electrode terminal sealing portion 52 of the positive electrode terminal member 50 and the first resin member 70 can be improved, and the sealing performance between the positive electrode terminal member 50 and the first resin member 70 can be particularly well maintained.

[0116] In addition, the above-mentioned negative electrode nano-pillars 65 are arranged on the surface 62m of the negative electrode terminal sealing portion 62 of the negative electrode terminal member 60, and the second resin material 85 is filled between these negative electrode nano-pillars 65, and the second resin member 80 is airtightly bonded to the negative electrode terminal sealing portion 62. Thus, the bonding strength between the negative electrode terminal sealing portion 62 of the negative electrode terminal member 60 and the second resin member 80 can be improved, and the sealing performance between the negative electrode terminal member 60 and the second resin member 80 can be particularly well maintained.

[0117] Next, a method for manufacturing the battery 1 will be described (see Figure 7 to Figure 10B ). First, prepare a shell cover member (shell member) 30Z before roughening. The shell cover member 30Z before roughening is obtained by punching an aluminum plate into a prescribed shape, forming a liquid injection hole 30k, a first insertion hole 30h1, a second insertion hole 30h2 and a safety valve 11 thereon. In addition, prepare in advance a positive terminal member (first terminal member) 50Z before roughening. The positive terminal member 50Z before roughening is obtained by punching an aluminum plate into a prescribed shape and performing a bending process. In addition, prepare in advance a negative terminal member (second terminal member) 60Z before roughening. The negative terminal member 60Z before roughening is obtained by punching a copper plate into a prescribed shape and performing a bending process.

[0118] Then, in the "positive electrode nanocolumn forming step (first nanocolumn forming step) S1" (refer to Figure 7 ), the positive terminal sealing portion 52 in the positive terminal member 50Z is irradiated with pulsed laser light LC while shifting the irradiation position (irradiating with pulsed laser light LC while moving the irradiation position) (refer to Figure 8 ), a forest of positive electrode nanorods 55 are formed on the surface 52m of the positive electrode terminal sealing portion 52. As for the positive electrode nanorods 55, as described above (also refer to Figure 4 ), the particles 55p formed by aluminum and aluminum oxide are connected in a rosary-like manner to form a columnar shape.

[0119] In the present embodiment, the laser irradiation conditions are as follows: the wavelength is 1064nm, the peak output power is 5kW, the pulse width is 150ns, the spacing pb is 75μm, and the spot diameter Db is 80μm. In the circular portion of the positive terminal sealing portion 52 irradiated with the laser LC when viewed from above, aluminum near the surface 52m is melted and then becomes aluminum vapor. Then, if the temperature of the vapor drops, it becomes particles 55p of aluminum and aluminum oxide, which accumulate on the surface 52m of the positive terminal sealing portion 52. By irradiating the laser LC on the positive terminal sealing portion 52 while staggering the irradiation position (irradiating the laser in a moving position), the particles 55p are stacked and combined in a rosary-connected manner to form a columnar shape, forming a forest of positive electrode nanocolumns 55.

[0120] In addition, in another "negative electrode nanocolumn forming step (second nanocolumn forming step) S2" (refer to Figure 7 ), the negative electrode terminal sealing portion 62 in the negative electrode terminal member 60Z is irradiated with pulsed laser light LC while shifting the irradiation position (see Figure 8 ), a forest of negative electrode nanorods 65 are formed on the surface 62m of the negative electrode terminal sealing portion 62. As for the negative electrode nanorods 65, as described above (also refer to Figure 4 ), the particles 65p formed by copper and copper oxide are connected in a rosary-like manner to form a columnar shape.

[0121] In the present embodiment, the laser irradiation conditions are as follows: the wavelength is 1064nm, the peak output power is 20kW, the pulse width is 50ns, the spacing pb is 60μm, and the spot diameter Db is 75μm. In the circular portion of the negative terminal sealing portion 62 irradiated with the laser LC when viewed from above, the copper near the surface 62m is melted and then becomes copper vapor. Then, if the temperature of the vapor drops, it becomes particles 65p of copper and copper oxide, which accumulate on the surface 62m of the negative terminal sealing portion 62. By irradiating the negative terminal sealing portion 62 with the laser LC while staggering the irradiation position (irradiating the laser in a moving position), the particles 65p are stacked and combined in a rosary-connected shape to form a columnar shape, forming a forest of negative electrode nanocolumns 65.

[0122] In addition, in another "cap nanocolumn forming step S3" (refer to Figure 7 ), the first cover sealing portion 31 of the housing cover member 30Z is irradiated with pulsed laser light LC while shifting the irradiation position (see Figure 8), a forest of first cover nanocolumns 35 are formed on the outer side surface 31m and the inner side surface 31n of the first cover sealing portion 31. In addition, the second cover sealing portion 32 in the housing cover member 30Z is also irradiated with pulsed laser LC while shifting the irradiation position, and a forest of second cover nanocolumns 36 are formed on the outer side surface 32m and the inner side surface 32n of the second cover sealing portion 32. As for the first cover nanocolumns 35 and the second cover nanocolumns 36, as described above (also refer to Figure 4 ), the particles 35p and 36p formed of aluminum and aluminum oxide are connected in a rosary-like manner to form a columnar shape. In this embodiment, the laser irradiation conditions are the same as the laser irradiation conditions in the positive electrode nanocolumn forming step S1.

[0123] Next, in the "second insert molding step S4" (refer to Figure 7 ), in a state where the negative terminal member 60 is inserted into the second insertion hole 30h2 of the case cover member 30, the second resin member 80 is insert-molded using a second resin material 85 having a resin material bending modulus E within the above range (see Fig.9A and Fig. 9B ).

[0124] Specifically, the second insert molding step S4 is performed using a molding die (not shown) having an upper die and a lower die. First, the case cover member 30 is arranged at a predetermined position of the lower die, and then the negative terminal member 60 is inserted into the second insertion hole 30h2 of the case cover member 30 (see Fig.9A ). Then, the upper mold is moved to the lower mold, and the molding mold is closed. Next, the molten second resin material 85 is injected into the mold cavity of the molding mold. At this time, the second resin material 85 is filled between the negative electrode nano-pillars 65 standing in the negative terminal sealing part 62, and between the second cover nano-pillars 36 standing in the second cover sealing part 32, and the second resin member 80 airtightly bonded to the negative terminal sealing part 62 and the second cover sealing part 32 is molded (refer to Fig. 9B ). Then, the cover assembly 15 in which the negative electrode terminal member 60 is fixed to the case cover member 30 via the second resin member 80 is taken out from the molding die.

[0125] Next, in the "first insert molding step S5" (refer to Figure 7 ), in the above-mentioned cap assembly 15, in a state where the positive terminal member 50 is inserted into the first insertion hole 30h1 of the housing cap member 30, the first resin member 70 is insert-molded using a first resin material 75 having a resin material linear expansion coefficient α within the above-mentioned range (refer to Fig. 10A and Fig. 10B ).

[0126] Specifically, the first insert molding step S5 is performed using a molding die (not shown) having an upper die and a lower die. First, the cap assembly 15 is arranged at a predetermined position of the lower die, and then the positive terminal member 50 is inserted into the first insertion hole 30h1 of the housing cover member 30 (see FIG. 1 ). Fig. 10A ). Then, the upper mold is moved to the lower mold, and the molding mold is closed. Next, the molten first resin material 75 is injected into the mold cavity of the molding mold. At this time, the first resin material 75 is filled between the positive electrode nano-pillars 55 standing in the positive terminal sealing part 52, and between the first cover nano-pillars 35 standing in the first cover sealing part 31, and the first resin member 70 airtightly joined to the positive terminal sealing part 52 and the first cover sealing part 31 is molded (refer to Fig. 10B Then, the cap assembly 16 (the cap assembly 16 in which the positive terminal member 50 is fixed to the case cover member 30 via the first resin member 70 and the negative terminal member 60 is fixed to the case cover member 30 via the second resin member 80) is taken out from the molding die.

[0127] Next, in the "electrode body connection step S6" (refer to Figure 7 ), an electrode body 40 obtained by stacking a positive electrode plate 41, a negative electrode plate 42 and a separator 43 is prepared, and the positive terminal inner side portion 53 of the positive terminal member 50 in the above-mentioned cap assembly 16 is welded to the positive electrode collector 40c of the electrode body 40. In addition, the negative terminal inner side portion 63 of the negative terminal member 60 in the cap assembly 16 is welded to the negative electrode collector 40d of the electrode body 40. Then, the electrode body 40 is wrapped with a bag-shaped insulating support 7.

[0128] Next, in the "electrode body accommodation and shell forming step S7", the shell body member 20 is prepared, the electrode body 40 covered with the insulating support 7 is inserted into the shell body member 20, and the opening 20c of the shell body member 20 is plugged with the shell cover member 30. Then, the opening 20c of the shell body member 20 and the peripheral edge 30f of the shell cover member 30 are laser welded airtightly around the entire circumference to form the shell 10 that accommodates the electrode body 40 inside.

[0129] Next, in the "liquid injection and sealing step S8", the electrolyte 5 is injected into the case 10 through the liquid injection hole 30k, so that the electrolyte 5 is impregnated into the electrode body 40. Then, the liquid injection hole 30k is covered from the outside with the sealing member 12, and the sealing member 12 and the case 10 are laser welded airtightly.

[0130] Next, in the "initial charging and aging step S9", a charging device (not shown) is connected to the battery 1 to perform initial charging on the battery 1. Then, the initially charged battery 1 is left to stand for a predetermined time to age the battery 1. In this way, the battery 1 is completed.

[0131] (Test results)

[0132] Next, the test results conducted to verify the effects of the present invention are described (refer to Figure 11 to Figure 14 ). First, the first resin member 70 of the positive electrode is insert-molded using a plurality of first resin materials 75 having different linear expansion coefficients α of the resin material. Specifically, for each first resin material 75, only the positive electrode nanocolumn forming step S1, the cover nanocolumn forming step S3, and the first insert molding step S5 are performed, and a cover assembly in which only the positive terminal member 50 is fixed to the shell cover member 30 via the first resin member 70 is obtained.

[0133] Then, for these cap assemblies, taking into account the operating temperature conditions of the battery, a hot and cold cycle test was performed in a temperature range of -40°C to 65°C. Specifically, using a liquid tank tester, the cap assembly was immersed in a liquid tank at -40°C for 3 minutes, and then immersed in a liquid tank at 65°C for 3 minutes. This cooling and heating was regarded as one cycle, and it was performed 3650 times. Then, for each cap assembly, the length of the crack generated in the portion near the boundary between the first resin member 70 and the positive terminal member 50 was measured. The results are shown together in Fig.11 In the case where no cracks occur in the first resin member 70, the length of the crack is 0.0 mm. Figure 12 to Figure 14 The same is true for the length of the cracks in the sample.

[0134] Depend on Fig.11 From the coordinate diagram, we can see that the linear expansion coefficient α of the resin material used is 1.5×10 -5 (1 / K) or less or 2.8×10 -5 When the first resin material 75 with a linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 When the first resin member 70 was molded with the first resin material 75 within the range of (1 / K) and subjected to a thermal cycle test, no cracks were generated in the first resin member 70. This shows that for the positive electrode, the linear expansion coefficient α of the first resin material 75 is set to 1.6×10 -5 ~2.7×10 -5 It is best to be within the range of (1 / K).

[0135] Next, a plurality of first resin materials 75 having different bending moduli E of the resin material were used to insert mold the first resin member 70. Then, the thermal cycle test was performed as described above, and the length of the cracks generated in the first resin member 70 was measured. The results are shown in FIG. Fig.12 . In addition, although detailed description is omitted, Fig.12 The linear expansion coefficient α of the first resin material 75 of each sample shown in FIG. 1 is within the above range (1.6×10 -5 ~2.7×10 -5 (1 / K)).

[0136] Depend on Fig.12 As can be seen from the coordinate diagram of FIG. 1 , the bending modulus E of the first resin material 75 has little effect on the presence or absence of cracks. Even if the bending modulus E of the first resin material is changed, cracks are generated in the first resin member 70. Therefore, in order to prevent cracks from being generated in the first resin member 70, the linear expansion coefficient α of the first resin material 75 is set to 1.6×10 -5 ~2.7×10 -5 It is best to be within the range of (1 / K).

[0137] Next, the second resin member 80 of the negative electrode is insert-molded using a plurality of second resin materials 85 having different bending moduli E of the resin material. Specifically, only the negative electrode nanocolumn forming step S2, the cover nanocolumn forming step S3, and the second insert-molding step S4 are performed for each second resin material 85, and a cover assembly 15 (see FIG. 1 ) in which only the negative electrode terminal member 60 is fixed to the case cover member 30 via the second resin member 80 is obtained. Fig. 9B ). Then, the above-mentioned thermal cycle test was performed on these cap assemblies 15, and the length of the cracks generated in the second resin member 80 near the boundary with the negative terminal member 60 was measured. The results are shown together in Fig.13 .

[0138] Depend on Fig.13 As can be seen from the coordinate graph, when the second resin member 80 is molded using the second resin material 85 having a resin material bending modulus E of 19 GPa or more and subjected to a thermal cycle test, cracks are generated in the second resin member 80. However, when the second resin member 80 is molded using the second resin material 85 having a resin material bending modulus E of 17 GPa or less and subjected to a thermal cycle test, no cracks are generated in the second resin member 80. It can be seen from this that for the negative electrode, it is preferable that the resin material bending modulus E of the second resin material 85 is 17 GPa or less.

[0139] Next, a plurality of second resin materials 85 having different linear expansion coefficients α were used to insert mold the second resin members 80. Then, the above-mentioned thermal cycle test was performed to measure the lengths of cracks generated in the second resin members 80. The results are shown in FIG. Fig.14 . In addition, although detailed description is omitted, Fig.14The magnitude of the resin material flexural modulus E of the second resin material 85 of each sample shown in is outside the above-mentioned range (17 GPa or less).

[0140] Depend on Fig.14 As can be seen from the coordinate diagram, the linear expansion coefficient α of the second resin material 85 has little effect on the presence or absence of cracks. Therefore, in order to prevent cracks from occurring in the second resin member 80, it is preferable to set the bending modulus E of the second resin material 85 to 17 GPa or less as described above.

[0141] As described above, in the manufacturing method of the battery 1, in the first insert molding step S5, the first resin member 70 is insert-molded using the first resin material 75 having the resin material linear expansion coefficient α within the above-mentioned range, so that cracks are unlikely to occur in the first resin member 70 during molding, and the sealing performance between the positive terminal member 50 and the first resin member 70 can be well maintained. In addition, in the second insert molding step S4, the second resin member 80 is insert-molded using the second resin material 85 having the resin material bending modulus E within the above-mentioned range, so that cracks are unlikely to occur in the second resin member 80 during molding, and the sealing performance between the negative terminal member 60 and the second resin member 80 can be well maintained.

[0142] The positive terminal member 50 made of aluminum has a larger linear expansion coefficient than the negative terminal member 60 made of copper. Therefore, if the first insert molding step S5 is performed first, cracks are likely to occur in the first resin member 70 due to the temperature change in the subsequent second insert molding step S4. In the present embodiment, the second insert molding step S4 is performed first, so in the second insert molding step S4, there is no first resin member 70 (see Fig.9A and Fig. 9B ), no cracks will be generated in the first resin member 70.

[0143] In addition, in the present embodiment, the positive electrode nano-column 55 is formed on the surface 52m of the positive electrode terminal sealing portion 52 by irradiating the laser LC as described above in the positive electrode nano-column forming step S1, so that the positive electrode nano-column 55 can be easily formed in the positive electrode terminal sealing portion 52. Moreover, in the first insert molding step S5, the first resin member 70 is molded while the first resin material 75 is filled between the positive electrode nano-columns 55, so that the bonding strength between the positive electrode terminal sealing portion 52 of the positive electrode terminal member 50 and the first resin member 70 can be improved, and the sealing performance between the positive electrode terminal member 50 and the first resin member 70 can be particularly well maintained.

[0144] In addition, in the negative electrode nanocolumn forming step S2, the laser LC is irradiated as described above to form the negative electrode nanocolumn 65 on the surface 62m of the negative electrode terminal sealing portion 62, so that the negative electrode nanocolumn 65 can be easily formed in the negative electrode terminal sealing portion 62. In addition, in the second insert molding step S4, the second resin member 80 is molded while the second resin material 85 is filled between the negative electrode nanocolumns 65, so that the bonding strength between the negative electrode terminal sealing portion 62 of the negative electrode terminal member 60 and the second resin member 80 can be improved, and the sealing performance between the negative electrode terminal member 60 and the second resin member 80 can be maintained particularly well.

[0145] As mentioned above, although this invention was demonstrated based on embodiment, this invention is not limited to embodiment, It is a matter of course that it can be applied with appropriate deformation|transformation within the range which does not deviate from the summary.

Claims

1. An electric storage device, comprising: a housing member having a first insertion hole and a second insertion hole; a first terminal member made of aluminum and inserted into the first insertion hole of the housing member; a second terminal member made of copper and inserted into the second insertion hole of the housing member; an insert-molded first resin member which insulates the housing member from the first terminal member and is airtightly bonded to the housing member to fix the first terminal member to the housing member; A second resin member that is insert-molded to insulate the housing member from the second terminal member and to airtightly bond the housing member and to fix the second terminal member to the housing member; The first resin member is made of a resin material with a linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 (1 / K) range (1.6×10 -5 ≤α≤2.7×10 -5 ), and the second resin member is composed of a second resin material different from the first resin material and having a resin material flexural modulus E of 17 GPa or less (E≤17).

2. The power storage device according to claim 1, wherein The first resin material includes a first thermoplastic main resin, a first thermoplastic elastomer, and a first filler, and the second resin material includes a second thermoplastic main resin, a second thermoplastic elastomer, and a second filler.

3. The power storage device according to claim 1 or 2, wherein: The first terminal member has a first terminal sealing portion, and the first resin member is airtightly joined to the first terminal sealing portion. On the surface of the first terminal sealing portion, particles containing aluminum and having a diameter of 100 nm or less are connected in a rosary-like manner to form a first nanocolumn forest having a columnar shape and a height of 50 nm or more. The first resin material is filled between the first nanocolumns that stand in a forest, and the first resin member is airtightly bonded to the first terminal sealing portion. The second terminal member has a second terminal sealing portion, and the second resin member is airtightly joined to the second terminal sealing portion. On the surface of the second terminal sealing portion, copper particles having a diameter of 100 nm or less are connected in a rosary-like manner to form a second nanocolumn forest having a columnar shape and a height of 50 nm or more. The second resin material is filled between the second nanocolumns that stand in a forest, and the second resin member is airtightly bonded to the second terminal sealing portion.

4. A method for manufacturing an electric storage device, the electric storage device comprising: a housing member having a first insertion hole and a second insertion hole; a first terminal member made of aluminum and inserted into the first insertion hole of the housing member; a second terminal member made of copper and inserted into the second insertion hole of the housing member; an insert-molded first resin member which insulates the housing member from the first terminal member and is airtightly bonded to the housing member to fix the first terminal member to the housing member; A second resin member that is insert-molded to insulate the housing member from the second terminal member and to airtightly bond the housing member and to fix the second terminal member to the housing member; The first resin member is made of a resin material with a linear expansion coefficient α of 1.6×10 -5 ~2.7×10 -5 (1 / K) range (1.6×10 -5 ≤α≤2.7×10 -5 ), The second resin member is made of a second resin material different from the first resin material and having a resin material bending modulus E of 17 GPa or less (E≤17), The method for manufacturing the power storage device comprises: a first insert molding step of insert molding the first resin member using the first resin material having a linear expansion coefficient α of the resin material, with the first terminal member inserted into the first insertion hole of the housing member; and The second insert molding step includes insert molding the second resin member using the second resin material having the resin material bending modulus E in a state where the second terminal member is inserted into the second insertion hole of the case member.

5. The method for manufacturing an electric storage device according to claim 4, wherein: The second insert molding step is performed first, and then the first insert molding step is performed.

6. The method for manufacturing an electric storage device according to claim 4 or 5, wherein: The first terminal member has a first terminal sealing portion, and the first resin member is airtightly joined to the first terminal sealing portion. On the surface of the first terminal sealing portion, particles containing aluminum and having a diameter of 100 nm or less are connected in a rosary-like manner to form a first nanocolumn forest having a columnar shape and a height of 50 nm or more. The first resin material is filled between the first nanocolumns that stand in a forest, and the first resin member is airtightly bonded to the first terminal sealing portion. The second terminal member has a second terminal sealing portion, and the second resin member is airtightly joined to the second terminal sealing portion. On the surface of the second terminal sealing portion, copper particles having a diameter of 100 nm or less are connected in a rosary-like manner to form a second nanocolumn forest having a columnar shape and a height of 50 nm or more. The second resin material is filled between the second nanocolumns that stand in a forest, and the second resin member is airtightly bonded to the second terminal sealing portion. The method for manufacturing the power storage device further includes: a first nanocolumn forming step, wherein, before the first insert molding step, the first terminal sealing portion of the first terminal member is irradiated with a pulsed laser while shifting the irradiation position, thereby forming a forest of the first nanocolumns in the first terminal sealing portion; and a second nanocolumn forming step, wherein, before the second insert molding step, the second terminal sealing portion of the second terminal member is irradiated with a pulsed laser while shifting the irradiation position, so as to form a forest of the second nanocolumns on the second terminal sealing portion; The first insert molding step fills the first resin material between the first nanocolumns standing in the first terminal sealing portion and molds the first resin member at the same time. The second insert molding step fills the second resin material between the second nano-columns standing in the second terminal sealing portion and molds the second resin member.

Citation Information

Patent Citations

  • Battery and battery manufacturing method

    JP2022079172A